FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN POSYANDU LANSIA DI PUSKESMAS TENAYAN RAYA PEKANBARU TAHUN 2018 - Rosmeri Br Bukit (Jurnal Kesehatan Husada Gemilang, 2022)
Elderly Posyandu is an integrated service post for the elderly in certain decided areas. It is the advancement of government policy thru the Health Center programs, and its implementation asks for the elderly, the families, the community leaders, and the social organizations participation. The aim of the research is to identify the factors that affect the elderly posyandu attendance at Tenayan Raya Health Center. The research was analytical descriptive with cross sectional observation and total sampling technique. The population of the research were all elderly people live near by the Tenayan Raya Health Center with a sample of 89 respondents which conducted on November 19, 2018. The data were analyzed over the univariate, bivariate, and multivariate data analysis. The results confirm that the visit behavior is good in majority (65 respondents or 73%), most of respondents have poor knowledge (49 respondents or 55.1%). The analysis of multivariate multiple logistic regression display the variable affects most is that of accessibility to posyandu (POR 12.444). The assumption of the research is that of attendance is at good category, but the accessibility to posyandu affects most the elderly to attend. It is consequently expected that the posyandu cadres boost advising or socializing about posyandu, and the place where it is held must be strategic and transportation runs well.